Didáctica de la lengua castellana como eje Dinamizador del desarrollo de competencias en educación básica - Herrera Becerra, María Olga; Balaguera Balaguera, Constanza (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This article presents a view about the teaching of the didactic of the Spanish Language in basic education based of the origin and the concept of the same, based on relevant theorists who have contributed to the construction of this discipline. In this article is presented a review since the approaches and principles used for the teaching of the Spanish language taking into account the advances and investigations carried out in this subject. Also It is aborded the didactic of the language, literature and the gramatical competence as main axes in the teaching of the mother language and as a basis for strengthening the four language skills developed by the speakers. Finally, It is made a reflection on the impact of the didactics of the Spanish language on the research carried out by the students of the program of the Basic education program with emphasis in Mathematics, Humanities and Spanish language of the Universidad Pedagógica y Tecnológica de Colombia.